Mapping Solar Energy Potential Based on Google Earth Engine (GEE) in West Sumatera Province - Haz, Fahrezy Maulana; Fajrin, Fajrin; Arini, Dwi; Armi, Ilham; Defwaldi, Defwaldi (Syntax Literate, 2025)
This study investigates the spatial distribution of solar energy potential in West Sumatera Province using Google Earth Engine (GEE) by integrating Himawari-8 and Sentinel-2 satellite data. The objectives are to identify regions with high solar irradiance and assess land use suitability for solar power plant development. Solar radiation models—DHI, DNI, and GHI—were computed and validated against NASA POWER data, achieving high model accuracy with RMSE values of 0.095, 6.43, and 0.05, and correlation coefficients of r = 0.93 across all models. The Mentawai Islands showed the highest GHI values (4,219.85 kWh/m²), while Dharmasraya had the highest DNI due to solar angle alignment. Land classification using Sentinel-2 imagery and the CART algorithm revealed that although 173,152.90 ha of forest land in West Siberut is highly irradiated, only 9.29 ha of nearby open land is recommended for development to minimize ecological impact. This integrative approach demonstrates how remote sensing and spatial modeling can inform sustainable energy planning. The findings provide a scalable framework for identifying viable sites for solar energy infrastructure in Indonesia, supporting both regional energy independence and national renewable energy targets.